Evidence Based Practice Beliefs and Implementation among Nurses in Nablus - Raneen Khateeb; Hadeel Alakhras; Dania Shirre; Bara'a Shater (My University, 2019)
Introduction Evidence-based practice (EBP) has been a priority in health care in recent decades. However, few studies have investigated EBP in clinical care, so we want to identify current state of nurses’ evidence-based practice competencies in Nablus, because of increase the quality of care and patient safety in healthcare, and health professionals are expected to implement evidence into their daily clinical practice and the believes EBP improve health care services. Aim The aims of the study are identify, evaluate and relation between beliefs and implementation of evidence based practice among nurses. Method This study is a quantitative cross-sectional survey which we used the questionnaire and demographic data among 152 nurses at four hospital in Nablus. Results In total, 136 nurses participated in the study (response rate 89%).There was a positive correlation (r) between beliefs towards evidence-based practice and implementation of evidence-based practice (r= .26,p< .018). Overall, participants had positive attitudes towards EBP and were willing to increase their knowledge to guide practice. However, they acknowledged poor implementation of EBP in daily practice. Conclusions Nurses in Nablus had a positive belief towards EBP and are inclined towards implementing evidence into their clinical practice but in small extent.
Keywords: Evidence-based practice (EBP), Implementation, Beliefs.